2020
DOI: 10.1038/s41477-020-0721-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of SERRATE via ubiquitin-independent 20S proteasome to survey RNA metabolism

Abstract: Serrate (SE) is a key factor in RNA metabolism. Here, we report that SE binds 20S core proteasome α subunit G1 (PAG1) among other components and is accumulated in their mutants. Purified PAG1-containing 20S proteasome degrades recombinant SE via an ATP- and ubiquitin-independent manner in vitro. Notwithstanding, PAG1 is a positive regulator for SE in vivo as pag1 shows comparable molecular and /or developmental defects relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(83 citation statements)
references
References 48 publications
7
62
2
Order By: Relevance
“…Moreover, we suggested that DCL1 can be degraded by an unknown protease during skotomorphogenesis and light/dark conversion ( 38 ). Furthermore, damaged SE is degraded by ubiquitin-independent proteasomal activity ( 39 ). Intriguingly, a recent study suggested that Dicer is cleaved by an unknown serine protease in undifferentiated monocytes ( 40 , 41 ).…”
mentioning
confidence: 99%
“…Moreover, we suggested that DCL1 can be degraded by an unknown protease during skotomorphogenesis and light/dark conversion ( 38 ). Furthermore, damaged SE is degraded by ubiquitin-independent proteasomal activity ( 39 ). Intriguingly, a recent study suggested that Dicer is cleaved by an unknown serine protease in undifferentiated monocytes ( 40 , 41 ).…”
mentioning
confidence: 99%
“…The interaction between FVE and DRB4 was further confirmed by the Co-IP assay with protein extracts from transfected N. benthamiana leaves ( Fig. 9B ) ( 39 ). Y2H and LCI assays for SGS3 and DRB4 also detected their interaction in vivo ( Fig.…”
Section: Resultsmentioning
confidence: 68%
“… ( A ) LCI assay showed that FVE (top) and FVE-8 (bottom) interact with DRB4 in N. benthamiana . PAG1-nLUC/cLUC-SE is a positive control ( 39 ). See also fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S5G). A recent study showed that SE contains an intrinsically unfolded region and undergoes degradation via the 20 S proteasome to secure the functionality of folded and functional SE ( 20 ). Hence, we suspected that RH6, RH8, and RH12 may facilitate the phase separation of SE during D-body assembly.…”
Section: Resultsmentioning
confidence: 99%